Lipid management for coronary heart disease patients: an appraisal of updated international guidelines applying Appraisal of Guidelines for Research and Evaluation II—clinical practice guideline appraisal for lipid management in coronary heart disease - Zhou, Huimin; Zhang, Shaozhao; Sun, Xiuting; Yang, Daya; Zhuang, Xiaodong; Guo, Yue; Hu, Xun; Du, Zhimin; Zhang, Meifen; Liao, Xinxue (Journal of Thoracic Disease, 2019)
Background: Clinical practice guidelines (CPGs) provide many recommendations for hyperlipidemia management, but some of them are still debatable. Methods: We applied the six-domain Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument to evaluate the quality of guidelines with lipid management recommendations for coronary heart disease (CHD), including dyslipidemia and CHD guidelines published from 2009 to 2019. Meanwhile, we synthesized and compared major recommendations and present the consistency and controversy in current dyslipidemia management. Results: Among 19 guidelines included, ten guidelines (“strongly recommended” with AGREE scores 61–94%) performed better than the other nine (38–65% as “recommended with some modification”) For blood lipid tests, most CHD guidelines simply required fasting sample while dyslipidemia guidelines preferred non-fasting sample except in high triglycerides state. Most guidelines consistently chose low-density lipoprotein cholesterol (LDL-C) as the primary lipid-lowering target (LLT), while non-high-density lipoprotein cholesterol (non-HDL-C) and apolipoprotein B were mainly selected as secondary LLTs. The specific goals of LDL-C lowering were either to lower than 70 mg/dL or with at least 50% reduction. All guidelines recommended high intensity or maximally tolerable doses of statins, while ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors were recommended as second-line therapy. Conclusions: The general quality of guidelines for lipid management is satisfactory. Consensus has been reached on the specific goal of lipid reduction and the intensity of statins therapy. Further research is needed to validate the application of non-fasting sample and non-HDL-C target, as well as the efficacy and safety of ezetimibe and PCSK9 inhibitors.